Acute exacerbations of interstitial lung disease: lessons from idiopathic pulmonary fibrosis. Issue 5 (September 2017) - Spagnolo, Paolo; Wuyts, Wim
Abstract : Purpose of review: The purpose of this review is to provide an update on acute exacerbation of interstitial lung disease (ILD), with a focus on idiopathic pulmonary fibrosis (IPF), in the light of the recently revised definition of acute exacerbation-IPF. Strengths and limitations of the current definition of acute exacerbation-IPF are also discussed. Recent findings: Clinically, acute exacerbation-IPFs are highly relevant events with a mortality rate of approximately 50%. A 2016 working group on acute exacerbation-IPF has suggested the definition be widened to include any acute respiratory worsening with new widespread alveolar abnormality on high-resolution computed tomography of the chest not fully explained by cardiac failure or fluid overload. Management of acute exacerbation-IPF typically includes supportive care, high-dose corticosteroids and broad-spectrum antibiotics, despite the scarcity of data supporting the usefulness of these therapies. The effect of a number of novel therapeutic approaches is currently under investigation. Summary: Acute exacerbation-IPF has recently been redefined. A standardized definition, similar to that of other chronic respiratory diseases, will likely facilitate the performance of highly needed studies in acute exacerbation of both IPF and other ILDs.